Marine survey unmanned surface vessel:platform design and application - Weiping WANG; Xi HE; Chao DONG; Bing ZHENG; Xue LI (Dianxin kexue, 2021)
Marine survey unmanned surface vessel (USV) has a wide range of applications.However, the attitude of USV is easily affected by wind, waves, currents and floating debris, which may cause structural damage or low precision observation.Double hull and wide deck platform of unmanned surface vessed was designed, and the transducer of multi-beam echo sounder was installed on the lifting mechanism.These designs improved the sailing attitude of the platform, the safety of the transducer and the accuracy of the observed data.In 2020, this USV was participated in the dike-inspection mission of Jiangxi’s emergency flood relief.It successfully inspected the sediment environment of 14 km dike, affected by the unfavorable working conditions like rapid water flow, turbid water and floating garbage.Four risks were located, which provided important data support for the anti-flood campaign.